Improvement of the Governance of the Company Using a Balanced Performance Card. Rafidain Bank is the Case Study - األشخاذ اىٍصاغد اىدنخٔر ٌطٍد ضصيَ ٌِٓو; األشخاذ اىٍصاغد اىدنخٔر ُاسي غتد اىصخار ٌطٍٔد; األشخاذ اىٍصاغد اىدنخٔر ْاشً فٔزي أىػتادي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Business organizations are still using the traditional method of preparing a balanced scorecard, and this has reflected on the efficiency of the work in these organizations. What is required is a move to use a comprehensive card that is more appropriate and consistent with the evolution of business management literature. Therefore, researchers focused on the introduction of balanced performance card to the management of business organizations as a solution to the problem of governance and work to improve them. Despite the emergence of the concept of the Balanced Scorecard, which has become widely applicable in business organizations since 1996, our organizations still do not realize the importance of this system as a planning and monitoring tool, not to mention the developments that have been achieved by the Balanced Scorecard. To the environment and society. It generally takes care of stakeholders who have been neglected in the balanced scorecard with four perspectives. Today's corporate leaders need a new set of tools that provides them with a greater vision for their organizations, including the company's governors. In light of the importance of research and its main directions, this research is designed to achieve the following objectives: 1. Understand the concept of the company's governance and its mechanisms. 2. To understand the concept of Balanced Scorecard and its counterpart.